You are on page 1of 9

1

Assignment 4 — Solutions 2/6/04

Problem 3.1

We have azimuthal symmetry and charge-free space so expand in Legendre polynomials as in eq. 3.33:

FHr, qL

F§

F§

r=a

r=b

=

=

=

AA l r l + B l r -Hl+1L E P l Hcos qL

l=0

V QJ ÅÅÅÅÅ - qN

p

2

V

p

QJq - ÅÅÅÅÅ N

2 z
V
a
b

ϖ

where Q is the step function. Use the orthogonality condition eq 3.21 to integrate both sides multiplied by P k Hcos qL:

l=0

1

AA l a l + B l a -Hl+1L E -1

Hcos qL P l Hcos qL P k Hcos qL

‚ AA l a l + B l a -Hl+1L E

l=0

2

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ 2 k + 1

d kl

A k a k + B k a -Hk+1L

=

=

=

1

-1 Hcos qL V QJ - qN P k Hcos qL

p

ÅÅÅÅÅ

2

V 0 1 Hcos qL P k Hcos qL

V

ÅÅÅÅÅÅÅ

2

H2 k + 1L 0 1 Hcos qL P k Hcos qL

The integral is done in Jackson 3.26 for odd k . For even k the P k HxL are even about x = 0, so we may double the integration range and take half of the result; also we gratuitously multiply by P 0 HxL = 1:

0

1

Hcos qL P k Hcos qL =

A k a k + B k a -Hk+1L

=

1

ÅÅÅÅÅ

2

V

ÅÅÅÅÅÅÅ

2

l

o

o

o

o

j

n

1

1

m

o

o

o

o

-1

Hcos qL P k Hcos qL P 0 Hcos qL = ÅÅÅÅÅ

2

i

jj-

k

1

ÅÅÅÅÅ

y

2 {

zz Hk-12 H2 k + 1L

z

d k0

Hk - 2L!!

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ 2 @Hk + 1L ê 2D!

2 d k0

,

k even

,

k odd

The same procedure works for the r = b boundary condition except we're now integrating over -1 § cos q § 0 on the right-hand-side, which can be evaluated by a change of integration variables cos qØ-cos q and noting that P k H-xL = H-1L k P k HxL (this is just a statement of the odd/evenness of the function):

2

A k b k + B k b -Hk+1L

Define

=

V

ÅÅÅÅÅÅÅ

2

H2 k + 1L -1 0 Hcos qL P k Hcos qL = - H2 k + 1L 1 0 Hcos qL P k H-cos qL

V

ÅÅÅÅÅÅÅ

2

= H-1L k

V

ÅÅÅÅÅÅÅ

2

H2

k + 1L 0 1 Hcos qL P k Hcos qL

= H-1L k

V

ÅÅÅÅÅÅÅ

2

l

o

o

o

o

m

o

o

o

o

n

i

j

jj-

k

1

ÅÅÅÅÅ

y

2 {

zz Hk-12 H2 k + 1L

z

d

k0

Hk - 2L!! ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ 2 @Hk + 1L ê 2D!

,

k even

, k odd

C k

ª

V

ÅÅÅÅÅÅÅ

2

l

o

o

o

o

m

o

o

o

o

n

i

j

jj-

k

1

ÅÅÅÅÅ

y

2 {

zz Hk-12 H2 k + 1L

z

A k a k + B k a -Hk+1L A k b k + B k b -Hk+1L

=

=

C k H-1L k C k

d k0

Hk - 2L!! ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ 2 @Hk + 1L ê 2D!

,

,

k even

k odd

ó

ó

A k + B k a -H2 k+1L A k + B k b -H2 k+1L

=

=

C k a -k

H-1L k C k b -k

ó

ó

A k a 2 k+1

+ B k

A k b 2 k+1 + B k

=

=

C k a k+1

H-1L k C k b k+1

Subtract the second row from the first to solve for A k and B k : =
A l
a l+1 - H-1L l b l+1
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
,
=
a -l - H-1L l b -l
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
C l
B l
C l
a 2 l+1 - b 2 l+1
a -H2 l+1L - b -H2 l+1L
V
FHr, qL
=
ÅÅÅÅÅÅÅ
+ ‚ AA l r l + B l r -Hl+1L E P l Hcos qL
2
l=1

I've separated out the A 0 =

b Ø ¶ this is like having no outer sphere and being outside a northern hemisphere at potential V , i.e. half of the a ê r version of eq. 3.36 superimposed with a constant potential +V . C l is independent of a and b, so we just need to worry about the limiting forms of A l and B l (keeping in mind that l ¥ 0 so apparently positive powers really are such):

a-b

ÅÅÅÅÅÅÅÅÅÅÅÅ

a-b

C 0 =

V

ÅÅÅÅÅÅ

2

and B 0 = 0 pieces to facilitate taking limits, which we will do next. For

lim

bØ¶ A l

lim

bØ¶ B l

=

=

lim

bØ¶

lim

bØ¶

l+1 êb l+1 - H-1L l

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

a 2 l+1 ê b l+1 - b l

a -l - H-1L l ê b l ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

a

C l

a -H2 l+1L - 1êb 2 l+1 C l

=

=

lim

bØ¶

0 - H-1L l ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ 0 - b l

a -l

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

a -H2 l+1L

C l

=

C l

=

0

a l+1 C l

,

l 0

The first few (nonzero, l > 0) C l 's are C 1 = 3ê 2 HV ê 2L, C 3 = -7 ê8 HV ê 2L, C 5 = 11 ê 16 HV ê 2L, so

bØ¶ FHr, qL

lim

=

C l J ÅÅÅÅÅ N l+1 P l Hcos qL

l=0

a

r

=

Å

ÅÅÅÅÅÅÅ V Å

Å

Å

Å

Å

ÅÅ

Ä

2

Ç

1 +

3

ÅÅÅÅÅ

2

J

a

ÅÅÅÅÅ

r

N 2 P 1 Hcos qL - J N 4 P 3 Hcos qL + ÅÅÅÅÅÅÅÅÅ J ÅÅÅÅÅ N 6 P 5 Hcos qL +

ÅÅÅÅÅ

8

a

ÅÅÅÅÅ

r

16

a

r

7

11

É

Ñ

Ñ

Ñ

Ñ

Ñ

Ñ

ÑÑ

Ö

exactly as advertised. For a Ø 0 this is like having no inner sphere and being inside a southern hemisphere at potential V , which is half of the r ê a version of eq. 3.36 superimposed with -V and with the substitution V Ø -V after that:

3

 1 l lim aØ0 A l lim aØ0 B l aØ0 lim FHr, qL = = = 0 - H-1L l b l+1 ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ 0 - b 2 l+1 C l = i jj- j k y z zz b { ÅÅÅÅÅ C l lim aØ0 ¶ ‚ l=0 a l+1 - a 2 l+1 H-1L l b -l ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ 1 - a 2 l+1 b -H2 l+1L C l V = 0 3 C l J- ÅÅÅÅÅ N l P l Hcos qL = ÅÅÅÅÅÅÅ 1 - ÅÅÅÅÅ P 1 Hcos qL + J N 3 P 3 Hcos qL - ÅÅÅÅÅÅÅÅÅ N 5 P 5 Hcos qL r b 2 Ä Å Å Å Å Å Å ÅÅ Ç ÅÅÅÅÅ 2 r b ÅÅÅÅÅ 8 r ÅÅÅÅÅ b 16 r J ÅÅÅÅÅ b 7 11 É Ñ Ñ Ñ Ñ Ñ Ñ ÑÑ Ö Problem 3.3 z x = zzˆ −=′ xx z 2 + ϖ 2 F§ q=pê2,r y
σ
x′=ϖ′ϖˆ′
x V

To find the coefficients we use the trick of calculating the potential at an arbitrary point z > R on the z-axis:

FHz z L

`

=

=

1

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

4 p e 0

3 x £ rHx ÷£ L

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

÷£ §

x ÷ - x

R

0

v £

1

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

4 p e 0

v £

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

0

R

p v £ f 0

v £

ì

2

=

s 0

ÅÅÅÅÅÅÅÅÅÅÅÅÅ

2

e 0

è!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!

R

2

z

2

+ HR - z LHv - Hv L

£

L

£

2

2

2

4

s 0 HR 2 - v £2 L -1ê2 Hz 2 + v £2 L 1ê2

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

change variable u ª v £2

s 0

= ÅÅÅÅÅÅÅÅÅÅÅÅÅ

=

4 e 0

ÅÅÅÅÅÅÅÅÅÅÅÅÅ s 0

4 e 0

R

0

2

1

u ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

è!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!

R

2

z

2

+ HR - z L u - u

2

2

2

Å Ä

Å

Å Å

Å

Å

Å Å

ÅÅ Ç

-sin -1

-2 u + R 2 - z 2

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

R 2 + z 2

Ñ É

R 2

ÑÑ Ñ Ö 0

Ñ

Ñ

Ñ Ñ

Ñ Ñ 4 e 0

s 0

ÅÅÅÅÅÅÅÅÅÅÅÅÅ

=

=

=

=

s

0

ÅÅÅÅÅÅÅÅÅÅÅÅÅ

4

e 0

i

j

j sinh -1 i j Â

j

jj

k

j

j

jj

k

R 2 - z 2 y ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ R 2 + z 2

{

z

z

z

zz - sin -1 H-1L z y

{

z

zz

z

R 2 - z 2 ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ R 2 + z 2

- Â ln i j Â

s

p

ÅÅÅÅÅ

2

0

ÅÅÅÅÅÅÅÅÅÅÅÅÅ

e 0

s

- ÅÅÅÅÅÅÅÅÅÅÅÅÅ

4

0

Ä

Å

Å

Å

Å

Å

Å

Å

Å

ÅÅ

Ç

j

j

jj

k

Â

z - R

Â ln ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

4 e 0

Â

z + R

+

2 R z

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

R 2 + z 2

y

z zz z z

{

É

Ñ

Ñ

Ñ

Ñ Ñ

Ñ Ñ

Ñ

ÑÑ Ö

=

=

s

0

ÅÅÅÅÅÅÅÅÅÅÅÅÅ

4

e 0

Ä

Å

Å

Å

Å

Å

Å

Å

Å

Å

Å

Å

Å

ÅÅ

Ç

-sin -1

-2 u + HR 2 - z 2 L ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

"#########################################

HR

2

2

L

2

- z

+ 4 R

z

2

2

R 2

É

Ñ

Ñ

Ñ

Ñ

Ñ

Ñ

Ñ

Ñ

Ñ

Ñ

Ñ

Ñ

ÑÑ 0

Ö

i

j j

j sin -1

jj
k

R 2 - z 2

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

R 2 + z 2

- sin -1 -2 R 2 + R 2 - z 2

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

R 2 + z 2

y

z

z

z

zz

{

=

s

0

ÅÅÅÅÅÅÅÅÅÅÅÅÅ

4

e 0

i

j

j

j

j

j ln j Â

j

j

j

j

jj

k

i

j

j

j

j

j

j

j

j

jj

k

R 2 - z 2 ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ R 2 + z 2

+ &'''''''''''''''''''''''''''''''''''

i

j

j

j

j

k

Â

R 2 - z 2 y ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ R 2 + z 2

z

z

z

z

{

2

+ 1

s

0

ÅÅÅÅÅÅÅÅÅÅÅÅÅ

4 e 0

i

j

j

k 2

p

ÅÅÅÅÅ

- Â ln

Â R + z ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ R + Â z {

z

z

y

ì

lnHL = -Â p ê 2

y

z

z

z

z

z

z

z

z

z

zz

{

+

p

ÅÅÅÅÅ

2

y

z

z

z

z

z

z

z

z

z

zz

{

Since the disk is at z = 0 has constant potential V , FH0L = V = p s 0 ê 4 e 0 so s 0 = 4 e 0 V ê p. Now to the cases:

(a)

1+e

For r > R, let u ª R ê z so 0 § u § 1 and we can expand about u = 0 using ln ÅÅÅÅÅÅÅÅÅÅÅ

1-e

= 2 n=0

e 2 n+1

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ :

2 n+1

4

F > Hz z L

`

=

Â

- ÅÅÅÅÅÅÅÅÅÅ

V

p

Â - u

ln ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

Â + u

=

Â V

- ÅÅÅÅÅÅÅÅÅÅ

p

1

+ Â u

ln ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

1

- Â u

=

2 Â V - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

p

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

2 l + 1

HÂ uL 2 l+1

l=0

=

2

- ÅÅÅÅÅÅÅÅÅÅÅÅ

V

p

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

2 l + 1

i

j

j

k

ÅÅÅÅÅÅ

z

H-1L l+1 R

l=0

z z y {

2 l+1

Now just take z Ø r and tack on the appropriate Legendre polynomials (remember that we want F to look like @A l r l + b l r -Hl+1L D P l eventually) for the general r > R solution: 2 V
H-1L l r
2 V
R
H-1L l R
j i
F > Hx ÷” L =
ÅÅÅÅÅÅÅÅÅÅÅÅ
„ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
J
ÅÅÅÅÅÅ
N -H2 l+1L P 2 l Hcos qL =
ÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅ
„ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
j
ÅÅÅÅÅÅ
z z y 2 l P 2 l Hcos qL
p
2 l + 1
R
p
r
2 l + 1
k
r {
l=0
l=0

(b)

(c)

For r < R, let u ª z ê R so 0 § u § 1 and expand about u = 0:

Â

V

Â u - 1

Â V

i

jjÂp+ ln ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zz = V + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

1 - Â u

y

2 HL V HuL 2 l+1

p

l=0

2 l + 1

 F < Hz z L ` ln ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ = j z = - ÅÅÅÅÅÅÅÅÅÅ - ÅÅÅÅÅÅÅÅÅÅ k + Â u { p Â u + 1 p 1 V + 2 V ¶ „ H-1L l+1 z ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ J ÅÅÅÅÅÅ N 2 l+1 = ÅÅÅÅÅÅÅÅÅÅÅÅ p 2 l + 1 R l=0 F < Hx ÷” L = V - 2 V ÅÅÅÅÅÅÅÅÅÅÅÅ ¶ „ H-1L l r ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ J ÅÅÅÅÅÅ N 2 l+1 P 2 l+1 Hcos qL p 2 l + 1 R l=0

To calculate capacitance set V = 1 and compute the total charge on the disk:

C

=

Q total § V=1

= 0

2 p v f 0 R v

ƒ ƒ

ƒƒ

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ §

è!!!!!!!!!!! !!!!!!! ƒ

s 0

R

2

- v 2

ƒƒ ƒ V=1

= 2 p

ƒ

4 e 0 V ƒ

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ §

ƒ

ƒ ƒ V =1 B- "########### #######

ƒ

R

2

-

v 2 F R

0

p

= 8 e 0 R

Problem 3.4

(a) We need to expand in spherical harmonics, but can take B lm = 0 since we want finiteness at the origin inside:

FHr, q, fL

=

l=0 m=-l

l A lm r l Y lm Hq, fL , Y lm Hq, fL = \$%%%%%%%%%%%%%%%%%%%%%%% ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

2 l + 1 ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

4 p

´¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨≠¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨Æ

ªC lm

Hl - %%%%%%%% mL! %%% % P l m Hcos qL Â m f

Hl + mL!

The boundary conditions are periodic with period 2 p ê n, so the potential should be as well:

FHr, q, f + 2 p ênL

=

FHr, q, fL

ï ‰ Â m Hf+2 pênL

=

Â m f

ï

2 Â p m ên

=

1

ï

mê n

œ

With the first segment at +V and alternating, the boundary condition is

FHa, q, fL

=

H-1L k V

, k p ê n §f§ Hk + 1L p ê n ,

Integrate the left- and right-hand sides:

k = 0, 1, …, 2 n - 1

5

0 2 p f -1

1 Hcos qL Y lm Hq, fL FHa, q, fL

*

=

0 2 p f -1

1

= A lm a l

Hcos qL Y lm Hq, fL‚

*

l

£

l £ =0 m £ =-l £

A l £ m £ a l £ Y l £ m £ Hq, fL

0 2 p f -1

1 Hcos qL Y lm Hq, fL FHa, q, fL =

*

n-1 k pên

2

k=0

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

n

Hk+1L p

1

f -1

Hk+1L p

= n-1 H-1L k V k pên

2

k=0

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

n

Hcos qL Y l £ m £ Hq, fLH-1L k V

*

f -1

1 Hcos qL C lm P l m Hcos qL -Â m f

2

1

n-1 H-1L k V C lm -1

k=0

Â

=

Hcos qL P l m Hcos qL ÅÅÅÅÅÅÅ

=

m

l

o

m

o

n

-Â p Hk+1L mên - -Â p k mên = -Â p k mên I -Â p mên - 1M

= H-1L k mên AH-1L mên - 1E

I -Â p Hk+1L mên - -Â p k mên M

0

2 H-1L k

,

,

m ê n even

m ê n odd

We see that A lm will vanish if m ê n is even. If m ê n is odd, we can have m either even or odd depending on n, i.e. schematically if n is odd, m = oddäodd = odd, otherwise if n is even, m = oddäeven = even. Also P l m is odd/even if m + l is odd/even, so the integral over it (and thus A lm ) will vanish if m + l is odd, which happens if m and l differ in parity. In summary, we must have all three of m, n, l be of the same parity if A lm is not to vanish. For these nonvanish- ing A lm we can do the sum over k immediately since the two H-1L k factors combine to form a +1:

 A lm a l = 2 1 n-1 H-1L k V C lm ‡ -1 - ‚ k=0 Â Hcos qL P l m Hcos qL 2 H-1L k ÅÅÅÅÅÅÅ m = -H2 n - 1 - 0 + 1L V C lm ‡ -1 1 Hcos qL P l m Hcos qL ÅÅÅÅÅÅÅÅÅ 2 Â m 4 Â n = - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ m V C lm ‡ -1 1 x P l m HxL A lm = l o o o oo m o o o o o n - 0 4 Â V ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ a l n ÅÅÅÅÅÅÅ m \$%%%%%%%%%%%%%%%%%%%%%%% ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ 2 l + 1 ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ 4 p Hl - mL! Hl + mL! %%%%%%%% %%% % 1 Hcos qL P l m Hcos qL , ‡ -1 , n, m, l have the same parity otherwise

(b) In the following we will need to evaluate integrals of P l m 's, which is a straightforward, tedious, and completely

uninteresting exercise so I ran them through Mathematica. We can save some work by using eq. 3.51 to relate

A l-m

=

=

4 Â V

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

a

l

4 Â V

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

a

l

n

ÅÅÅÅÅÅÅ

m

n

ÅÅÅÅÅÅÅ

m

\$%%%%%%%%%%%%%%%%%%%%%%% ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

2 l + 1

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

4 p

Hl + mL!

Hl - mL!

%%%%%%%% %%% % 1 Hcos qL P l -m Hcos qL

-1

\$%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%

2 l + 1

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

4 p

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

Hl + mL! H-1L m Hl - mL!

Hl - mL!

Hl + mL!

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

1

-1

Hcos qL P l m Hcos qL

= -H-1L m+1

4 Â V ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

n

ÅÅÅÅÅÅÅ

a

l

m

= H-1L m+1 A lm

\$%%%%%%%%%%%%%%%%%%%%%%% ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

2 l + 1

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

4 p

Hl - mL!

Hl + mL!

%%%%%%%%%%% % 1 Hcos qL P l m Hcos qL

-1

n = 1 is odd, so we will only have terms where m and l are both odd. The above then gives A l-m = A lm for all l, m since m + 1 is even. Remembering that l ¥ 0 and m = -l, …, l , we see that the nonzero coefficients up to l = 3 are

6

A

A

A

11

33

31

=

=

=

4

Â V

- ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

-

4

a

Â V

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

a

3

4 Â V

- ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

a 3

1

ÅÅÅÅÅ

1

1

ÅÅÅÅÅ

3

1

ÅÅÅÅÅ

1

\$%%%%%%%%%%%%%%%%%%%%%%% %%%% %%%%%%

2 + 1

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

4

p

H1 - 1L!

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

H1 + 1L!

\$%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%

6 + 1

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

4

p

H3 - 3L!

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

H3 + 3L!

\$%%%%%%%%%%%%%%%%%%%%%%% %%%% %%%%%%

6

+ 1

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

4

p

H3 - 1L!

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

H3 + 1L!

1

-1

Hcos qL P 1 1 Hcos

qL

1 Hcos qL P 3 3 Hcos qL

-1

=

=

1 Hcos qL P 3

-1

1

Hcos qL =

Â V

- ÅÅÅÅÅÅÅÅÅÅ

a

\$%%%%%% 6

ÅÅÅÅÅ

p

Â

V

ÅÅÅÅÅÅÅÅÅÅ

a

Â V

3

ÅÅÅÅÅÅÅÅÅÅ

a 3

è!!!!!!!!!! 35 p

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

16

è!!!!!!!!!! 21 p

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

16

J- N = ÅÅÅÅÅÅÅÅÅÅ

ÅÅÅÅÅ

2

a

p

Â V

=

A 3-3

= A 31

FHr, q, fL

=

Â V j j \$%%%%%%%%%% ÅÅÅÅÅÅÅÅÅÅ 3 p

i

j j

j

j

k

2

r

ÅÅÅÅÅ

a

è!!!!!!!!!! 35 p

@Y 1-1 Hq, fL + Y 11 Hq, fLD + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ J ÅÅÅÅÅ N 3 @Y 3-3 Hq, fL + Y 33 Hq, fLD

16

r

a

+

è!!!!!!!!!! 21 p

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

16

J

r

ÅÅÅÅÅ

a

y

z z

z

z

z

N 3 @Y 3-1 Hq, fL + Y 31 Hq, fLD z +

{

\$%%%%%%%%%% ÅÅÅÅÅÅÅÅÅÅ 3 p

2

=

A 1-1

In our coordinate system the "right" hemisphere is at +V and F is explicitly specified for the full range of q and f. The result eq 3.36 has the northern hemisphere at +V and gives the potential F £ as a function of q £ only, since there is azimuthal symmetry in their case. A little thought shows that if we take the q = p ê 2 "slice" of our system and shift f Ø p ê 2 - f we will have rotated into their coordinate system with our shifted f playing the role of q £ . Now

In our coordinate system the "right" hemisphere is at +V and F is a function of both q and f. The result eq 3.36 has the northern hemisphere at +V and gives the potential F £ as a function of q £ only, since there is azimuthal symmetry in their case. A little thought shows that if we take the q=p ê 2 "slice" of our system and shift fØp ê 2 - f we will have rotated into their coordinate system with our shifted f playing the role of q £ . A formula from my CRC handbook helps (if marginally) cut down on the algebra: z
-V
θ
x
θ′
φ
x
+V

Y lm J

Y

11 J

33 J

Y

31 J

Y

p

ÅÅÅÅÅ

2 ,

p

ÅÅÅÅÅ

2

Y lm J

p

ÅÅÅÅÅ

2

,

p

- fN + Y l-m J ÅÅÅÅÅ

2 ,

p

ÅÅÅÅÅ

2

p

ÅÅÅÅÅ

2

- \$%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%% %%%%%%%%

fN

%%%%%

H2 l + 1LHl - mL! Hl + mL!

=

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

4 p

H-1L Hl+m2 Â m Hpê2-fL

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

2 l I ÅÅÅÅÅÅÅÅÅÅÅÅ M! I ÅÅÅÅÅÅÅÅÅÅÅÅ M!

2

2

l-m

l+m

H-1L lê2 è!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!! H2 l + 1LH